Pengaruh Komunikasi dan Kelekatan Orang Tua - Remaja Terhadap Self Esteem Remaja Pada Keluarga Utuh Dan Tunggal - Rachmawati Hadori; Dwi Hastuti; Herien Puspitawati (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2019)
Adolescence is a period of transition from children to adults which self-esteem is important to be developed. Adolescence is considered as one of the main and dominant processes of social and psychological growth of personality. This study examines the influence of parents-adolescent communication and attachment on adolescents’ self-esteem in intact and single-parent families. The research was conducted in public and private high schools and vocational schools in the city of Bekasi, both those who have and do not have PIK-R. Respondents in this study were adolescents in SMA A, SMK A, SMA B and SMK B in the City of Bekasi. Taking school samples is done purposively. The population of this study was 687 people. Based on predetermined criteria, namely students of class X - XII with an age range of 14-19 years from selected schools in the city of Bekasi, then respondents selected from intact and single families then obtained the number of samples as many as 200 people who fit the criteria. Data processing is done by using descriptive analysis and inferential analysis (independent T-Test and multiple linear regression test). The results showed that family status had a significant positive effect on adolescent self esteem. Parent-teen communication has a significant positive effect on adolescent self esteem. Parent-adolescent attachment has a significant positive effect on adolescent self esteem. The implications of research, adolescents are expected to improve self esteem, especially in adolescents from a single family, for example, changing negative perceptions to positive (feeling yourself useless, worthless to be useful and valuable for others).